Analysis Of The Development Of The Kanigoro District As The New Capital City In Blitar Regency - Liza Rosyidatun Ni'mah; Yana Syafriyana Hijri; Asep Nurjaman (Publik : (Jurnal Ilmu Administrasi), 2023)
Blitar Regency is one of the regencies that has a fairly rapid development. However, in his government has not stood in its own territory. The activities of the Blitar Regency Government are still one in the Blitar City area. Therefore, to improve the condition of its government, Blitar Regency needs to develop its territory. In accordance with the ratification of Government Regulation No. 3 of 2010 concerning the relocation of the capital city of Blitar Regency to its own territory, Kanigoro District. This study aims to analyze the extent of the development of Kanigoro District as the new capital city in Blitar Regency. The method used in this research is a qualitative method with qualitative descriptive analysis techniques. The data collection techniques used are observation, interviews, or document review. The results of this study indicate that the relocation of the capital city of Blitar district is one of the government's efforts to create equitable development. In addition, the transfer is carried out so that government services are more effective and efficient. This Regional Displacement and Development is based on a strong policy. In the process of development, the government has made plans in several documents. Although in its implementation there are still some obstacles.